2019
DOI: 10.1002/anie.201900782
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of (+)‐Sarcophytin, (+)‐Chatancin, (−)‐3‐Oxochatancin, and (−)‐Pavidolide B: A Divergent Approach

Abstract: A concise and divergent approach for the total syntheses of four cembrane diterpenoids, namely (+)‐sarcophytin, (+)‐chatancin, (−)‐3‐oxochatancin, and (−)‐pavidolide B, has been developed, and it also led to the structural revision of (−)‐isosarcophytin. The key steps of the strategy feature a double Mukaiyama Michael addition/elimination, a Helquist annulation, two substrate‐controlled facial‐selective hydrations, and a pinacol rearrangement. The described syntheses not only achieved these natural products in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…However,s ubjection of mesylate 26 to various Lewis acids [7a] resulted in decomposition, and an intramolecular aldol cyclization occurred to give pentacycle 27 under basic conditions.P leasingly,t he corresponding triflate 26' ' without isolation was capable of transformation into the anticipated product 27' ' in the presence of tBuOK/tBuOH in 69 %yield. [24] Finally,aregioselective formation of the D 8,9 -olefin was achieved through Mukaiyama dehydrogenation procedure, [25] accompanied by epimerization at C11 to furnish (À)-pavidolide B(5,ORTEP drawing, Scheme 5) [15] in 75 %y ield. Despite initial failures in the direct lactonization of 27' ' by Mitsunobu reaction, the intramolecular S N 2c yclization of the corresponding mesylate delivered 29 with low efficiency(< 10 %yield), which was likely due to the steric effect from the equatorial isopropyl group at C1.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 4 more Smart Citations
“…However,s ubjection of mesylate 26 to various Lewis acids [7a] resulted in decomposition, and an intramolecular aldol cyclization occurred to give pentacycle 27 under basic conditions.P leasingly,t he corresponding triflate 26' ' without isolation was capable of transformation into the anticipated product 27' ' in the presence of tBuOK/tBuOH in 69 %yield. [24] Finally,aregioselective formation of the D 8,9 -olefin was achieved through Mukaiyama dehydrogenation procedure, [25] accompanied by epimerization at C11 to furnish (À)-pavidolide B(5,ORTEP drawing, Scheme 5) [15] in 75 %y ield. Despite initial failures in the direct lactonization of 27' ' by Mitsunobu reaction, the intramolecular S N 2c yclization of the corresponding mesylate delivered 29 with low efficiency(< 10 %yield), which was likely due to the steric effect from the equatorial isopropyl group at C1.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[22] Subsequently,anumber of reducing reagents such as Zn-(BH 4 ) 2 ,NaBH 4 /Et 3 B, l-Selectride,DIBAL-H, and SmI 2 were screened for the regio-and diastereoselective reduction of the ketone at C11, and either caused the over-reduction to yield amixture of isomeric triols or gave exclusively the trans-diol C11-epi-8 (ORTEP drawing, Scheme 5). [15] Fortunately,itwas found that by treatment of 25 with NaBH 4 in pyridine, [23] 8 was obtained as amajor isomer in 78 %yield, setting the stage for the challenging pinacol rearrangement. However,s ubjection of mesylate 26 to various Lewis acids [7a] resulted in decomposition, and an intramolecular aldol cyclization occurred to give pentacycle 27 under basic conditions.P leasingly,t he corresponding triflate 26' ' without isolation was capable of transformation into the anticipated product 27' ' in the presence of tBuOK/tBuOH in 69 %yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations